Weed incidence and sowing time affect soybean development - Schievenin, Luciano; Caron, Braulio Otomar; Elli, Elvis Felipe; Schwerz, Felipe; Rockenbach, Ana Paula; Orsolin da Silva, Diecson Ruy (Comunicata Scientiae, 2018)
Despite the economic importance of the effects of weeds on the plastochron and emission of nodes of soybean plants, it has not been studied in detail. The aim of this study was to provide information about the effects of weeds on the development of soybean plants by determining the plastochron and number of nodes of soybean plants of different cultivars sown at different times in soils with presence and absence of weeds. A field study was conducted during the 2013/2014 crop season including a phytosociological survey to identify the occurring weeds, and the determination of the plastochron and final number of nodes of soybean plants. Four botanical families of weeds were found infesting the soybean crops. The plastochron and final number of nodes of soybean were influenced by the cultivar, sowing time, and presence of weeds. The plastochron was higher when the plants were grown in the presence weeds due to the higher relative frequency, relative density, relative abundance, and importance value index of the Euphorbia heterophyla, Ipomoea purpurea, and Urochloa plantaginea species, which resulted in a slower development of the soybean plants, and lower number of nodes per plant.